2007
DOI: 10.1007/bf02685922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different selenium sources on tissue selenium concentrations, blood GSH-Px activities and plasma interleukin levels in finishing lambs

Abstract: Thirty-two wether lambs of Tan sheep were randomly assigned into four dietary treatment groups (eight per group) for an 8-wk study and then fed a basal diet deficient in Se (0.06 mg/kg) or diets supplemented to provide 0.10 mg/kg Se from sodium selenite, selenized yeast, and seleniumenriched probiotics, respectively. Blood samples were collected at d 0, 28, and 56 of the experiment and tissue samples were collected at experiment termination. Tissue and blood Se concentrations, blood glutathione peroxidase (GSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
48
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 31 publications
15
48
1
4
Order By: Relevance
“…Similar results were reported by Qin et al (2007). However, Van Ryssen et al (1989) and Gunter et al (2003) found no differences in the GPx activity in whole blood of animals given organic or inorganic selenium.…”
Section: Rumen Blood Enzymes Ruminantsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results were reported by Qin et al (2007). However, Van Ryssen et al (1989) and Gunter et al (2003) found no differences in the GPx activity in whole blood of animals given organic or inorganic selenium.…”
Section: Rumen Blood Enzymes Ruminantsupporting
confidence: 84%
“…Qin et al (2007) also showed a significantly higher whole blood selenium concentration and GPx activities in lambs fed Se-yeast enriched diet (0.10 mg/kg of diet) compared to lambs fed similar concentrations of sodium selenite. The differences in results obtained by the researchers might be explained by the fact that although whole blood Se concentration is closely correlated with the GPx activity (Brigelius-Flohe et al 1994), there is evidence that the percentage of Se in erythrocytes associated with GPx may vary depending on the Se source (Belstein and Whanger 1986;Van Ryssen et al 1989).…”
Section: Glutathione Peroxidase Activity In Bloodmentioning
confidence: 85%
See 1 more Smart Citation
“…Studies with both dairy cows and beef cattle have shown that SY is more efficiently absorbed and assimilated than -E-mail: d.t.juniper@rdg.ac.uk inorganic Se, as SeMet can be taken up via methionine transporter mechanisms within the gastro-intestinal tract and non-specifically incorporated into body proteins in place of methionine (Weiss, 2003), resulting in elevated concentrations of Se in both milk (Juniper et al, 2006) and body tissues (Qin et al, 2007). Surai (2006) reported that SeMet is retained in tissue proteins to a greater extent than selenocysteine (SeCys) or Se derived from inorganic forms.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the inorganic form is not utilized as effi ciently as the organic form [6]. Moreover, organic forms of Se are absorbed and retained more readily by ruminants than inorganic forms [11]. Therefore, recent studies have focused on comparing both these forms [12,13].…”
Section: Introductionmentioning
confidence: 99%